The Future of Foreign Aid - Sumner, A. author. aut Link
XII, 101 p.
Keywords: Sumner and Mallett review the literature on aid in light of shifts in the aid system and the increasing concentration of the world's poor in middle-income countries. As a consequence, they propose a series of practical, policy relevant options for future development cooperation, with the aim of provoking discussion and informing policy.